Fluorous Phase‐Directed Peptide Assembly Affords Nano‐Peptisomes Capable of Ultrasound‐Triggered Cellular Delivery. Issue 38 (16th August 2017) - Medina, Scott H.; Michie, Megan S.; Miller, Stephen E.; Schnermann, Martin J.; Schneider, Joel P.
Abstract: Here, we report the design, synthesis and efficacy of a new class of ultrasound (US)‐sensitive self‐assembled peptide‐based nanoparticle. Peptisomes are prepared via templated assembly of a de novo designed peptide at the interface of fluorinated nanodroplets. Utilizing peptide assembly allows for facile particle synthesis, direct incorporation of bioactive sequences displayed from the particle corona, and the ability to easily encapsulate biologics during particle preparation using a mild solvent exchange procedure. Further, nano‐peptisome size can be precisely controlled by simply modulating the starting peptide and fluorinated solvent concentrations during synthesis. Biomolecular cargo encapsulated within the particle core can be directly delivered to the cytoplasm of cells upon US‐mediated rupture of the carrier. Thus, nano‐peptisomes represent a novel class of US‐activated carriers that can shuttle cell‐impermeable biomacromolecules into cells with spatial and temporal precision. Abstract : Burst your bubble : The templated assembly of a de novo designed peptide at the interface of fluorous nanodroplets affords ultrasound‐sensitive nano‐peptisomes. Acoustic rupture of the carrier at the surface of cells leads to direct intracellular delivery of encapsulated membrane‐impermeable biomolecular cargo with spatial and temporal precision.